ANTILEISHMANIAL EPIDIOXYSTEROLS FROM THE COLOMBIAN MARINE SPONGE Ircinia campana ARE OXIDATION PRODUCTS FROM NATURALLY OCCURRING Δ5,7 STEROLS - MÁRQUEZ F., Diana M.; MARTÍNEZ M., Alejandro (Vitae, 2009)
Marine sponges of the genus Ircinia are known to contain several classes of metabolites, some of them with interesting biological activities as furanesesterterpenes, polyprenylated hydroquinones, macrolides, sulfur containing terpenoids, and steroids with various patterns of oxidation. In our search for antiparasitic metabolites from marine sponges, we found that the Colombian Caribbean sponge Ircinia campana contains a complex mixture of epidioxysterols which displayed antileishmanial activity. This paper demonstrates that epidioxysterols found in this sponge are photo-oxidation products from the naturally occurring Δ5,7 sterols. These results suggest that epidioxysterols reported previously in sponges of the genus Ircinia are not naturally occurring products, so they are not valid chemotaxonomic markers for the sponges of this genus.